The Dance of Illusive Perception - Jayasekera, Ranadeva (My University, 2021)
Let’s do a small thought experiment. We conceptualise the world through the information we get from our sensory organs, and a complex deductive process carried out by our brain. Let’s for simplicity focus on our vision, and information and deduction process associated. So, for argument’s sake, this person has one sensory organ, the eye, but rational can be extended to all other organs that make up a complete human. We ‘see’ an object when essentially 3 ingredients sync together. (1) A particle or a wave emerging from the relevant object (2) The wave connecting to the eye as the sensory organ (3) the nerve system that communicates this signal to the brain, and the brain that then compares the attributes of the information contained in this signal with a pre-established database and giving a certain conclusion or perception . The final artefact of this process is that one sees or recognises the relevant object (e.g. car) and the whole process takes place in a tiny infinitesimally small time scale, and we deduce the time lapse as instantaneous.
PRESENTED